A critical review of the effect of teacher preparedness on students’ academic achievement: A research agenda - Kiamba, Elizabeth Welu; Mutua, Francis (My University, 2017)
This is a critical review of teacher preparedness investigating the origin of teacher preparedness, the concept of teacher preparedness, academic achievement, and its effect on students’ academic achievement, the theoretical framework and any gaps through desk research. In most of the studies examined for the purpose of this paper, teacher preparedness was used as an independent variable and academic achievement as dependent variable. It was identified that though studies have been done on effect of teacher preparedness on students’ academic achievement on different subjects none has been done on Kiswahili subject. Therefore the researchers will intend to study the effect of teacher preparedness on students’ academic achievement in Kiswahili language and find out if the findings on the other subjects in Kiswahili language. The theories which will be used to back the research include Teacher Efficacy and Walberg theories
Keywords: Teacher preparedness; Academic achievement; teaching and learning process